Issue salience of Facebook users in Egypt: an agenda-setting experiment - Visonà, Mark (AUC Knowledge Fountain, 2012)
This study explores issue salience among Egyptian Facebook users during the parliamentary elections of December 2011. The researcher examines the potential of agenda-setting effects occurring from the use of social media as an information source. In this study, a field experiment with a pretest/posttest design was conducted on 71 undergraduates of the American University in Cairo. Participants were assigned to treatment groups, some of which were exposed to media concerning the issue of ignorance/illiteracy in Egypt. This exposure was an attempt to increase the salience of the issue for Facebook users. The study also examined the relationship between demographic factors and issue salience in order to rule out confounding variables affecting the results. Few statistically significant results were found yet the presence of issue-related media did raise the issue salience for participants in the treatment groups. Some demographic factors were found to be associated with issue salience, and the conclusions recommend stratifying treatment groups. The data suggest that further investigation into agenda-setting and social media is warranted, and the study identifies several potential areas and avenues for future research.